Using action research to teach students to manage team learning and improve teamwork satisfaction - Scott-Ladd, Brenda; Chan, C. (Sage Publications Ltd., 2008)
This article reports on a study investigating strategies that students can use to develop skills in managing team learning. Two groups of second-year management students participated in a semester long action research project over two semesters. The students were educated on team development, team processes and conflict management and how to review and enhance team development. Teachingstaff supported the approach and students were regularly encouraged to reflect on and learn about how their behaviour contributed to team effectiveness. This approach encouraged student participation andownership as well as early intervention if problems arose. Findings suggest that when students are taught to manage the processes of teamwork and take greater ownership of managing conflict and teamrelations they report less conflict and less social loafing and are more satisfied with their learning outcomes.